The Impact and Outcomes of Integrating Health Literacy Education Into Adult Basic Education Programs in Boston - Marcia Drew Hohn; Lorna Rivera (SLACK Incorporated, 2019)
Background: Adult basic education (ABE) is the national system that offers educational services in English language development, reading, writing, math, technology, and communications to adults with low literacy, limited English, or both. These services range from basic levels to high school equivalency, with specialty programs in transition to community colleges and family literacy. Objective: This study sought to analyze the role of ABE in increasing health literacy among low literate and limited English populations and to identify effective models for teaching and learning about health in this setting. Methods: During a 2-year period, 90 students from three ABE programs in Boston participated in health literacy classes focused on healthy eating and received prevention screening services through local public health organizations. The majority of students classified themselves as Black, African American, or Latino. Participants ranged in age from 18 to 35 years; 64% of the participants were women. The three research sites were located in the Roxbury neighborhood of Boston, where health disparities and poverty rates are disproportionately high. During the study period, researchers conducted semi-structured interviews with teachers (N = 12) from each of the participating classrooms to gather information about the students in their health classes. Researchers also conducted semi-structured interviews and focus groups (N = 9) with students at each site during the study period to examine how they described changes in their knowledge, attitudes, and actions regarding health. Researchers also conducted ethnographic field research by observing health classes at each site, which was supplemented by collecting teachers' lesson plans as well as materials produced by learners. Key Results: ABE programs are a good setting for adults with limited literacy or limited English to increase their health literacy. The programs, which provide steady learning environments over time with staff skilled in adult learning, allow students to engage with health information in the context of their everyday lives, thereby increasing the likelihood of healthier practices. Conclusions: ABE programs play a vital role in developing health literacy among low literacy populations and are part of the solution for addressing health disparities.